2021
DOI: 10.3390/jcm10184120
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparison of the Effect of Inotropes on Cardiorenal Syndrome in Patients with Advanced Heart Failure: A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Prevention of cardiorenal syndrome through treatment with inotropic agents remains challenging. This network meta-analysis evaluated the safety and renoprotective effects of inotropes on patients with advanced heart failure (HF) using a frequentist random-effects model. A systematic database search was performed until 31 January 2021, and a total of 37 trials were included. Inconsistency, publication bias, and subgroup analyses were conducted. The levosimendan group exhibited significantly decreased mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
(108 reference statements)
1
9
0
Order By: Relevance
“…Levosimendan reduced ICU stay significantly ( p < 0.038), whereas dobutamine decreased the duration of hospital stay ( p < 0.015), a finding in alignment with that of Chen and co-workers [ 77 , 78 ] above. There was a progressive decline in serum creatinine in the levosimendan group.…”
Section: In the Presence Of Renal Dysfunction/failuresupporting
confidence: 85%
See 1 more Smart Citation
“…Levosimendan reduced ICU stay significantly ( p < 0.038), whereas dobutamine decreased the duration of hospital stay ( p < 0.015), a finding in alignment with that of Chen and co-workers [ 77 , 78 ] above. There was a progressive decline in serum creatinine in the levosimendan group.…”
Section: In the Presence Of Renal Dysfunction/failuresupporting
confidence: 85%
“…Chen et al [ 77 ] produced a network meta-analysis in March 2020 with a report on renal dysfunction in patients undergoing cardiac surgery and later added a second report based on 37 published studies that included 4957 patients [ 78 ], most of whom were classified as having advanced heart failure. A feature of this research was its use of P -scores to provide relative rankings of the efficacy of interventions.…”
Section: In the Presence Of Renal Dysfunction/failurementioning
confidence: 99%
“…16 Our findings in patients with severe renal dysfunction differed from the conclusion of the aforementioned NMA that "levosimendan is a safe drug for patients with cardiorenal syndrome." 7 However, the RCTs included in this analysis excluded patients with renal failure, and all reported mean baseline sCr of the included patients only increased slightly. There remains a gap in evidence about the effectiveness and safety of levosimendan in patients with severe renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Using only indirect evidence that is susceptible to confounding, the latest network meta-analysis (NMA) found that, compared with milrinone, levosimendan more significantly reduced mortality. 7 The included studies of the NMA about levosimendan were published more frequently and more recently (26 trials, between 2000 and 2019) than those about milrinone (4 trials, between 1987 and 2002), and different clinical practices in different periods may affect the outcome variables. Moreover, in the included trials of the NMA, there were 2 of 26 levosimendan trials compared with 3 of 4 milrinone trials with high risks of bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation